Virulence related characteristics of epidemiologically important Yersinia enterocolitica strains - Saikia, G K; Thapliyal, D C (The Indian Journal of Animal Sciences, 2012)
Strains (11) of Yersinia enterocolitica belonging to 4 pathogenic serogroups (0; 3, 0; 5, 27, 0; 8, and 0; 9) were screened for 10 virulence related characteristics. Marked agreement in the results obtained through tests for calcium dependence (CD), autoagglutinability (AA) and production of man nose resistant haemagglutinin (MRHA) was recorded. A strain (Ye-10) of group 0:3 considered epidemiologically important, showed enterotoxic activity without manifesting any of the major virulence related characteristic. A strain of group 0: 8 (Ye-11) tested positive for all the virulence related markers (including HeLa cell invasiveness and mouse lethality) but was not enterotoxic. While CD, AA and MRHA can be relied to detect virulent strains more frequently, it is desirable to use a battery of in-vitro and in-vivo tests for the detection of virulence in Y. enterocolitica. The presence of a cytotoxic factor in Y. enterocolitica is indicated.